Paul’s Iconic Christ among Mediterranean Cult Statues: A Comparison of Divine Images - Chantziantoniou, Alexander (Journal for the study of the New Testament, 2025)
While scholars continue to debate whether Paul ever explicitly called the messiah a god, there can be no question that he called the messiah an image of a god (2 Cor. 4.4). Even so, there has been no shortage of comparative studies that situate Paul’s messiah among ancient Mediterranean gods, including the Jewish god himself, whereas what is arguably more proximate comparanda for Paul’s iconic claims tend not to be taken into consideration, namely, ancient Mediterranean images of gods. Taking for granted that Paul’s god—the Jewish god—was a Mediterranean god among others, in this article I redescribe Paul’s messiah as a Mediterranean cult image among others. By exploring the relation between gods and their images, between divinity and materiality, with images of gods as material media that make present the gods they image, new light is cast on the debated relation between the Jewish god and his christological image in Paul’s letters.